2011
DOI: 10.1088/0004-637x/741/2/113
|View full text |Cite|
|
Sign up to set email alerts
|

Starless Cloud Core L1517b in Envelope Expansion With Core Collapse

Abstract: Various spectral emission lines from the star-forming molecular cloud core L1517B manifest red asymmetric double-peaked profiles with stronger red peaks and weaker blue peaks, in contrast to the oft-observed blue-skewed molecular spectral line profiles with blue peaks stronger than red peaks. Invoking a spherically symmetric general polytropic hydrodynamic shock model for the envelope expansion with a core collapse (EECC) phase, we show the radial flow velocity, mass density, and temperature structures of a se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…Such coexistence of inward and outward motions in star-forming molecular clouds or cores may be the "envelope expansion with core collapse (EECC)" (Gao & Lou 2010;. The clouds or cores B68 (Lada et al 2003), SFO 11NE (Thompson & White 2004), L1495A-N, L1507A, L1512 (Lee et al 2001), L1517B (Fu et al 2011), and L1689-SMM16 (Chitsazzadeh et al 2014) were also shown relative to the reports.…”
Section: Envelope Expansion With Core Collapsementioning
confidence: 91%
“…Such coexistence of inward and outward motions in star-forming molecular clouds or cores may be the "envelope expansion with core collapse (EECC)" (Gao & Lou 2010;. The clouds or cores B68 (Lada et al 2003), SFO 11NE (Thompson & White 2004), L1495A-N, L1507A, L1512 (Lee et al 2001), L1517B (Fu et al 2011), and L1689-SMM16 (Chitsazzadeh et al 2014) were also shown relative to the reports.…”
Section: Envelope Expansion With Core Collapsementioning
confidence: 91%
“…For quasi-spherical molecular clumps in hydrodynamic evolution, it is possible to use at least four major observational diagnostics to constrain self-consistent dynamic models coupled with radiative transfer calculations (e.g. Fu et al 2011), namely, extensive observations of various properties of molecular lines (e.g. line profiles), submillimeter continuum emissions from thermal dusts, and dust extinction observations as well as neutral hydrogen 21 cm absorption lines in MCs.…”
Section: Static Bonnor-ebert Sphere Modelmentioning
confidence: 99%
“…As with other cores, estimates of its physical properties are subject to the molecular tracer. For instance, the mass and radius for this core varies between ~ 0.05 M ⊙ and ~ 0.06 pc(Benson & Myers 1989) to ~ 1.7 M ⊙ (Kirk et al 2005) and ~ 3.89 M ⊙ (Fu et al 2011). The gas temperature for this core has been reported to be ~ 9 K (Tafalla et al 2002; Keto & Field 2005).…”
Section: Resultsmentioning
confidence: 99%
“…A starless core that is probably experiencing a breathing mode, i.e. exhibiting signs of in-fall close to the centre, but has an expanding envelope (Keto & Field 2005; Fu, Gao, & Lou 2011). As with other cores, estimates of its physical properties are subject to the molecular tracer.…”
Section: Resultsmentioning
confidence: 99%